1996
DOI: 10.1007/bf02088746
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of interleukin-4 and -10 in inflammatory bowel disease

Abstract: The pathogenesis of ulcerative colitis (UC) and Crohn's disease (CD) may be associated with a decreased production of cytokines suppressing macrophage and T-cell functions: interleukins (IL) -4 and IL-10. Serum concentrations of IL-4 and IL-10 were measured using an ELISA technique, and intestinal IL-4 and IL-10 mRNA was detected by a reverse transcriptase polymerase chain reaction (RT-PCR) in 34 patients with inflammatory bowel disease (IBD) (20 with UC and 14 with CD) and compared to 12 control subjects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 40 publications
3
22
1
Order By: Relevance
“…These observations are in agreement with previous studies [44,45]. It has also been reported that patients with IBD produce lower amounts of IL-10 [46,47]. Our findings of a decreased IL-1b induction in patients with IBD are in line with a recent study showing a failure of acute inflammation in CD patients due to the presence of diminished concentrations of inflammatory markers like IL-8 and IL-1b [48].…”
Section: Discussionsupporting
confidence: 96%
“…These observations are in agreement with previous studies [44,45]. It has also been reported that patients with IBD produce lower amounts of IL-10 [46,47]. Our findings of a decreased IL-1b induction in patients with IBD are in line with a recent study showing a failure of acute inflammation in CD patients due to the presence of diminished concentrations of inflammatory markers like IL-8 and IL-1b [48].…”
Section: Discussionsupporting
confidence: 96%
“…The reverse anti-inflammatory action is provided by IL-4 and IL-10. IL-4 is able to block antibody-dependent cytotoxicity as well as to suppress the spontaneous and induced production of IL-1β, TNF-α, PGE 2, IL-6, IL-8, and nitric oxide [18].…”
Section: Discussionmentioning
confidence: 98%
“…In partial support of this concept, a decrease in the expression of IL-4 mRNA has been detected in the intestinal tissue recovered from patients with Crohn's disease, but not ulcerative colitis [121]. In an attempt to enhance expression of IL-4 systemically, the murine IL-4 transgene was expressed by adenoviral gene therapy in a rat model of colonic immune activation and inflammation (trinitrobenzene sulfonic acid-induced colitis) [122].…”
Section: Il-4 In the Pathogenesis Of Ibdmentioning
confidence: 97%